Dynamic Capability Strategy in Technology-Based Companies: Enhancing Innovation, Organizational Adaptability, and Sustainable Competitive Advantage - Mayra Dania; Zara Khadijah; Atiyyatullah Atiyyatullah; Qudrah Qudrah; Sadia Hira (Journal on Economics, Management and Business Technology, 2026)
Rapid technological advancement, digital transformation, artificial intelligence, and increasing global competition have significantly intensified environmental uncertainty for technology-based companies. In such dynamic business environments, organizations must continuously adapt to technological change, market disruption, and evolving customer demands to sustain long-term competitiveness. This study aims to analyze dynamic capability strategies in technology-based companies and evaluate how sensing capability, seizing capability, and transforming capability contribute to organizational competitiveness, innovation performance, organizational performance, and business sustainability. The study employed a quantitative research approach using an explanatory survey design involving managers and executives from technology-based companies operating in software development, artificial intelligence, FinTech, cloud computing, digital platforms, and technology-oriented small and medium-sized enterprises. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all three dimensions of Dynamic Capability significantly and positively influence organizational outcomes, with transforming capability demonstrating the strongest effect on organizational performance and long-term business sustainability. Sensing capability enhances organizations' ability to identify technological opportunities and market changes, while seizing capability improves strategic resource allocation and innovation implementation. The study concludes that the integration of sensing, seizing, and transforming capabilities enables technology-based companies to effectively respond to environmental changes, accelerate innovation, and maintain sustainable competitive advantage. The findings contribute to the advancement of Dynamic Capability Theory by demonstrating the complementary nature of its core dimensions and provide practical guidance for managers and policymakers in developing adaptive strategies, strengthening organizational learning, promoting digital transformation, and enhancing long-term organizational resilience in the digital economy.